Eurycomanone and Eurycomanol from Eurycoma longifolia Jack as Regulators of Signaling Pathways Involved in Proliferation, Cell Death and Inflammation - Hajjouli, Shéhérazade (Molecules, 2014)
Eurycomanone and eurycomanol are two quassinoids from the roots of Eurycoma longifolia Jack. The aim of this study was to assess the bioactivity of these compounds in Jurkat and K562 human leukemia cell models compared to peripheral blood mononuclear cells from healthy donors. Both eurycomanone and eurycomanol inhibited Jurkat and K562 cell viability and proliferation without affecting healthy cells. Interestingly, eurycomanone inhibited NF-κB signaling through inhibition of IκBα phosphorylation and upstream mitogen activated protein kinase (MAPK) signaling, but not eurycomanol. In conclusion, both quassinoids present differential toxicity towards leukemia cells, and the presence of the α,β-unsaturated ketone in eurycomanone could be prerequisite for the NF-κB inhibition.